Archetype and Individuation Process in Alan Wake (2010) Video Game: Game and Psychoanalytic Studies - Andry Garcia (Journal of Games, Game Art, and Gamification, 2022)
This research purpose aims to demonstrate the individuation process of Alan Wake through the archetypes by finishing the last page of â€œDepartureâ€ manuscript. The research uses interpretative qualitative method in extending the findings. Using interpretation analysis can depict phenomenon of video game from the act, figures, sources (game items; weapons, flashlight, manuscript, etc.), situation, by applying Carl Gustav Jungâ€™s psychoanalytic theory of archetype and individuation process in the video game. In the video game story, Alan Wake is a writer who had had a writerâ€™s block for 2 years and experiences a nightmare. The nightmare happens when Alice Wake has lost at the Cauldron Lake. To find Alice, Alan follow the journey from his nightmare, suddenly discovers something powerful to create and change things influenced by two mythical figures, namely Thomas Zane and Barbara Jagger. Both figures come into Alanâ€™s nightmare following the unwritten manuscript â€œDepartureâ€ plot story, whose Alan is guided to contain several figures to overcome darkness figures and integrate light and darkness to be actualized. The findings show that archetype depictions are associated by mythological images reflected from the collective unconscious in Alan Wake. The forms such as Barbara Jagger, Thomas Zane, Taken, Alan as The Hero, and the Bird Leg cabin are the projected images that Alan created in his dream. Alan starts his nightmare journey, experiences all the archetypes contributed, and realizes how to end the â€œDepartureâ€ manuscript as Alanâ€™s individuation process. In conclusion, Alan Wake's unconscious journey by ending at the point of self-realization and writing the "Departure" script is considered as an individuation process.